Read It Yourself : Astronauts - Level 1 - Ladybird (Bharat Ladybird, 2015)
How do astronauts get in to space and what do they do there? Find out about rockets, space stations and how to sleep in space. For over thirty-five years, the best-selling Read it yourself with Ladybird has helped children learn to read. All titles feature essential key words. Title-specific words are repeated to practise throughout. Designed to be read independently at home or used in a guided reading session at school. All titles include comprehension questions of puzzles, guidance notes and book band information for schools. This Level 1 title is suitable for very early readers who are ready to take their first steps in reading. A small number of frequently repeated words, simple facts, clearly labelled images and captions fully engage the reader. Includes contents, index and a picture glossary.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction; PY UOI - How The World Works - Exploration -- PY UOI - How The World Works - Exploration